Studi Karakteristik Pejalan Kaki di LampuPenyeberangan Ruas Jl. Jend. Sudirman - Fiki Na`amJulianto (Universitas Putra Indonesia YPTK Padang, 2020)
Pedestrians are part of a transportation system that is no less important than other modes of transportation. Therefore pedestrian needs are an integral part of the road transportation system. Based on the results of an evaluation of the behavior of pedestrian crossers on the Jalan Jend section. Sudirman on the influence of traffic, which can be concluded from this study is on the Jalan Jend segment. Sudirman during the hours of 06.00 - 08.00 that the crossing uses more roads than crossing through the zebra crossing in the morning and the zebra crossing in the crossing lights can be concluded to function ineffectively, on the Jalan Jend segment. Sudirman during 16.00 - 18.00 more crossers using zebra crossing than crossing through roads in the morning and zebra crossing in crossing lights can be concluded to function effectively, during the morning peak the average pedestrian crossing that passes through the road influences the performance of the current traffic where it is able to hold 1 vehicle for 1.03 seconds and during the afternoon peak the average pedestrian crosser that passes through the road affects the performance of traffic flow which is able to hold 2 vehicles for 1.53 seconds.